Polish Jews in the Soviet Union (1939-1959) : history and memory of deportation, exile, and survival - Friedla, Katharina; Nesselrodt, Markus, 1984- (Jews of Poland., 2021)
"The majority of Poland's prewar Jewish population managed to survive World War II and the Holocaust in the interior of the Soviet Union. This collection of original essays tells the story of more than 200,000 Polish Jews who came to a foreign country as war refugees, forced laborers, or political prisoners. This diverse set of experiences is covered by historians, literary and memory scholars, and sociologists who specialize in the field of East European Jewish history and culture"--